Effects of multiple handstrippings of channel catfish (Ictalurus punctatus) females induced to ovulate with carp pituitary extract on production of channel catfish female x blue catfish (I. furcatus) male hybrid fry. Issue 4 (1st October 2016) - Dunham, Rex A.; Kim, Soonhag; Su, Baofeng; Argue, Brad J.; Ligeon, Carel; Ramboux, Anne C.
ABSTRACT: Channel catfish ( Ictalurus punctatus ) females were injected with carp pituitary extract (CPE) and were multiple handstripped three times to harvest eggs. Eggs were fertilized with sperm from blue catfish ( I. furcatus ) to produce channel-blue hybrid (CB hybrid) embryos and fry. A higher number of females yielded eggs ( P < .05) during the first stripping attempt (90.3 ± 1.1% [mean ± SE]) than during the second (67.6 ± 2.1%) and third attempts (7.6 ± 0.5%). Significant differences also were observed for the number of eggs/kg stripped between the first (5, 471 ± 225) and second (2, 598 ± 97) and the first and third (1, 302 ± 46) strippings. Percent fertilization (71.5 ± 2.7 %) was higher ( P < .05) for the first stripping than the second and third strippings, but the second stripping (58.2 ± 1.8%) was not different from the third (51.7 ± 1.6%). The hatching percent of embryos did not vary among the three times strippings. The fry/kg female body weight produced was higher ( P < .05) for the first (1, 399 ± 112) than the second (471 ± 26) and third strippings (28 ± 2). It is productive to strip the females a second time, as fry production can be increased by 33.7% by waiting 5 h and harvesting the additional eggs ready at that time. The time and effort for a third stripping is not worthwhile because of the low percentage of females releasing eggs at that time and the low fry output.